INOVASI MANAJEMEN MUTU PENDIDIKAN ISLAM DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DAN DAYA SAING PADA ERA DIGITAL DI SMA KUN KARIMA PANDEGLANG - Amin Munawir; M. Muslim; Samudi (ADDABANA: Jurnal Pendidikan Agama Islam, 2026)
Innovation in Islamic education quality management in the digital age requires a comprehensive approach, combining technology with strong Islamic values. This management innovation focuses not only on the use of technology, but also on curriculum development, teachers' digital competencies, and Islamic education quality management systems that are relevant to the digital age. The purpose of this study is to examine and analyze innovations in Islamic education quality management in improving learning quality and competitiveness in the digital era, emphasizing aspects of form and strategy as well as challenges. This study uses a phenomenological qualitative approach with data collection through observation, interviews, and documentation, and data analysis using data reduction, data presentation, and conclusion drawing. The findings of this study can be summarized as follows:  Forms of innovation in Islamic education quality management to improve learning quality in the era of digital education include: the use of Islamic-based e-learning platforms, the integration of digital technology into the Islamic education curriculum, the development of digital competencies for teachers, and the implementation of project-based learning with an Islamic approach.  Meanwhile, innovation strategies in Islamic education quality management to improve learning quality in the digital education era include: the application of Islamic e-learning-based learning technology, strengthening teachers' competencies in digital literacy and educational technology, developing an integrative curriculum with a digital and Islamic approach, and project-based learning that integrates Islamic values. The challenges in innovating Islamic education quality management to improve learning quality in the digital education era are: limited access to technology and digital infrastructure, lack of digital competence among educators, curriculum gaps between Islamic content and modern technology, and cultural barriers and perceptions regarding the use of technology in Islamic education. To overcome these challenges, comprehensive efforts are needed, such as improving infrastructure, intensive training for educators, curriculum adjustments, and a more inclusive approach to integrating technology with Islamic values in the Islamic education process.